2008
DOI: 10.1007/s00253-008-1542-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of phycocyanin—a pigment with applications in biology, biotechnology, foods and medicine

Abstract: C-phycocyanin (C-PC) is a blue pigment in cyanobacteria, rhodophytes and cryptophytes with fluorescent and antioxidative properties. C-PC is presently extracted from open pond cultures of the cyanobacterium Arthrospira platensis although these cultures are not very productive and open for contaminating organisms. C-PC is considered a healthy ingredient in cyanobacterial-based foods and health foods while its colouring, fluorescent or antioxidant properties are utilised only to a minor extent. However, recent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
325
0
25

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(352 citation statements)
references
References 132 publications
2
325
0
25
Order By: Relevance
“…It has also been reported that the amino acid pattern of these microalgae could be comparable with or superior to that of other vegetable foods and feeds, and that they have a high nutrient digestibility (Spolaore et al, 2006;Plaza et al, 2009;Alvarenga et al, 2011). In addition, spirulina contains substances such as pigments (for example carotenoids such as β-carotene and zeaxanthin) (Maoka, 2011), phycobiliproteins (for example phycocyanin, which is unique in the cyanobacteria (Eriksen, 2008), vitamins (Becker, 1994), macro and micro mineral elements (Becker, 1994;Spolaore et al, 2006) and antioxidants (Christaki et al, 2013). These compounds reveal potential biological properties such as antimicrobial, antioxidant, anti-cancer and anti-inflammatory or act as immune enhancers and colorants (Freitas et al, 2012;Batista et al, 2013;Christaki et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…It has also been reported that the amino acid pattern of these microalgae could be comparable with or superior to that of other vegetable foods and feeds, and that they have a high nutrient digestibility (Spolaore et al, 2006;Plaza et al, 2009;Alvarenga et al, 2011). In addition, spirulina contains substances such as pigments (for example carotenoids such as β-carotene and zeaxanthin) (Maoka, 2011), phycobiliproteins (for example phycocyanin, which is unique in the cyanobacteria (Eriksen, 2008), vitamins (Becker, 1994), macro and micro mineral elements (Becker, 1994;Spolaore et al, 2006) and antioxidants (Christaki et al, 2013). These compounds reveal potential biological properties such as antimicrobial, antioxidant, anti-cancer and anti-inflammatory or act as immune enhancers and colorants (Freitas et al, 2012;Batista et al, 2013;Christaki et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…The two subunits form ␣␤ monomers, which aggregate into ␣ 3 ␤ 3 trimers and further into disc-shaped ␣ 6 ␤ 6 hexamers, the functional unit of phycocyanin (Eriksen, 2008). It has good therapeutic values, such as antioxidative, immunomodulating, anti-cancer, antiviral, anti-allergic, anti-mutagenic, anti-inflammatory, hepatoprotective, blood vessel-relaxing and blood lipid-lowering activities (Thangam et al, 2013), which made it a better active ingredient in functional food.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of phycobiliproteins Cyanobacterial phycobiliproteins are classified into three main groups: C-phycocyanin (dark cobalt blue, λmax = 610 − 620 nm), allophycocyanin (brighter aqua blue, λmax = 650 − 655 nm) and phycoerythrin (bright pink, λmax = 540 − 570 nm) depending on the inherent color and absorbance properties (Eriksen, 2008). Quantitative evaluation of C-phycocyanin, allophycocyanin and phycoerythrin content was performed in edible cyanobacteria Nostochopsis sp.…”
Section: Resultsmentioning
confidence: 99%
“…Our preliminary studies suggested that Nostochopsis cells contain substantial amounts of phycobiliproteins, which act as light-harvesting accessory pigments. C-phycocyanin (blue pigment protein) (Eriksen, 2008) in particular has been reported as a potent peroxy radical scavenger (Bhat and Madyasha, 2000), platelet aggregation inhibitor (Chiu et al, 2006) and proliferation inhibitor of cancer cells (Lin et al, 2000) in vitro and in vivo. The therapeutic activity of Nostochopsis sp.…”
Section: Introductionmentioning
confidence: 99%